2004
DOI: 10.1007/s00432-004-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of screening for hepatocellular carcinoma

Abstract: Our finding indicated that biannual screening reduced HCC mortality by 37%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
975
3
28

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,186 publications
(1,017 citation statements)
references
References 12 publications
11
975
3
28
Order By: Relevance
“…These results are consistent with several previous studies exploring evolutionary temporal trends in HCC. The role of HCC surveillance in chronic liver disease has become well established over the years, with benefits reported in several studies 42, 43, 44. Similarly, a significant improvement in diagnostic modalities, such as dynamic computerized tomography, contrast‐enhanced magnetic resonance imaging, and ultrasound, has also played an important role in detecting HCC earlier 35.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with several previous studies exploring evolutionary temporal trends in HCC. The role of HCC surveillance in chronic liver disease has become well established over the years, with benefits reported in several studies 42, 43, 44. Similarly, a significant improvement in diagnostic modalities, such as dynamic computerized tomography, contrast‐enhanced magnetic resonance imaging, and ultrasound, has also played an important role in detecting HCC earlier 35.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of surveillance programs has still to be demonstrated through prospective RCTs, comparing the survival of participants with or without surveillance, though they may be susceptible to lead-time bias. To date, there is only one study that has proved the benefit of surveillance [139]. Zhang et al [139] recruited 18,186 patients with chronic hepatitis due to HBV in China.…”
Section: Rationale For Surveillancementioning
confidence: 99%
“…To date, there is only one study that has proved the benefit of surveillance [139]. Zhang et al [139] recruited 18,186 patients with chronic hepatitis due to HBV in China. The study revealed that surveillance with biannual AFP measurement and US reduced the mortality from HCC by 37% in spite of the fact that the compliance of scheduled tests was only 58.2%.…”
Section: Rationale For Surveillancementioning
confidence: 99%
“…During the past 20 years, major efforts have been made to identify patients at risk of developing HCC, and screening programs for detecting HCC have been introduced. 9,10 Currently, approximately half of patients with HCC who receive care at referral centers and a considerably smaller proportion of patients in community practices are diagnosed at an early stage before cancer-related symptoms have developed.…”
Section: Rationale For Advocating Liver Transplantation For Hccmentioning
confidence: 99%